The Meaning Of Bali Aesthetic Code In The Animated Film Si Uma - Hasbullah Hasbullah; I Wayan Mudra; I Wayan Swandi (Pascasarjana Institut Seni Indonesia Surakarta, 2021)
This study aims to analyze the meaning of aesthetic code in the animated film